THE RELEVANCE OF SOCIAL THEORY IN LEARNING THE QUR'AN AND HADITH - M Jadid Khadavi; Nadiah Yusfi Nabilah (PT Innovative Academic Journals, 2025)
This study aims to examine the relevance of social theories in increasing the effectiveness of learning the Qur'an and Hadith (Qurdis). Qurdis learning, as part of Islamic religious education, has an important role in shaping students' character and religious understanding. However, conventional learning methods often pay less attention to social aspects and interaction in the learning process. This research uses a qualitative approach with a literature study method. Data were collected from various sources such as books, scientific journals, articles, and other relevant sources that discuss social theories and their implementation in education, especially in Qurdis learning. The results of the study indicate that relevant and applicable social theories in the context of Qurdis learning, such as social learning theory (Bandura), constructivism theory (Piaget, Vygotsky), symbolic interactionism theory (Mead), and social cognitive learning theory (Bandura) make a major contribution to the development of more effective, relevant, and appropriate Qurdis learning. student needs through in-depth understanding.